No Differences in Levels of Circulating Progenitor Endothelial Cells or Circulating Endothelial Cells Among Patients Treated With Ticagrelor Compared With Clopidogrel During Non–ST‐Segment–Elevation Myocardial Infarction. Issue 19 (2nd October 2018) - Diego‐Nieto, Alejandro; Vidriales, Maria B.; Alonso‐Orcajo, Norberto; Moreno‐Samos, Jose C.; Martin‐Herrero, Francisco; Carbonell, Raul; Cid, Belen; Cruz‐Gonzalez, Ignacio; Martin‐Moreiras, Javier C.; Cuellas, Carlos; Pascual, Cristina; Lopez‐Benito, Maria; et al.
Abstract : Background: Ticagrelor use during acute coronary syndromes demonstrated a decrease in all‐cause mortality in the PLATO (Platelet Inhibition and Patient Outcomes) trial. This effect has been attributed to a non–platelet‐derived improvement in endothelial function. The aim of this study was to determine differences in the number of endothelial progenitor cells and/or circulating endothelial cells found in peripheral blood in patients treated with either ticagrelor or clopidogrel during non–ST‐segment–elevation myocardial infarction. Methods and Results: In this multicenter, randomized study (NCT02244710), patients were considered for inclusion after non–ST‐segment–elevation myocardial infarction whenever they were P2Y12 ‐inhibitor naïve. Ticagrelor and clopidogrel were allocated at a 1:1 ratio. Blood samples for determining endothelial progenitor cells and circulating endothelial cells were extracted before the antiplatelet loading dose, 48 hours after presentation of index symptoms, and 1 month after the event. A multichannel cytometer was used for optimal cell characterization. A total of 96 patients fulfilled the inclusion criteria. Circulating endothelial cell levels corrected by white blood cells were as follows at baseline, 48 hours, and 1 month: 44 (28–64), 50 (33–63), and 38 (23–62) cells/mL, respectively, for clopidogrel and 38 (29–60), 45 (32–85), and 35 (24–71) cells/mL, respectively, for ticagrelor ( P =0.6). Endothelial progenitor cell levels were 29 (15–47), 27 (15–33), and 18 (10–25) cells/mL, respectively, for clopidogrel and 20 (11–33), 22 (12–32), and 18 (11–29) cells/mL, respectively, for ticagrelor ( P =0.9). No differences in intraindividual changes were found. Conclusions: Patients treated with ticagrelor during non–ST‐segment–elevation myocardial infarction, in comparison to clopidogrel, showed similar levels of endothelial progenitor cells and circulating endothelial cells. These data suggest that the endothelial protective effect mediated by ticagrelor is not related to bone marrow physiology modulation. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02244710.